From Awareness to Action: An Empirical Study of How Green Advertising Influences Purchase Intentions Through Green Brand Image (Journal of Asian Development Studies, 2025)
Sustainable consumption is reclaiming its position as a marketing trend in developing countries such as Pakistan. This paper assesses the extent to which the effect of green advertising and green brand awareness on customer purchasing intention is mediated by green brand image. It aims to fill the current gap in knowledge regarding how the relationship between green marketing strategies and consumer behaviour works, and it also provides ideas on how to reach the ecologically conscious consumer. It is theorised in the proposed model that the purchase intention directly relies on the green advertising and brand awareness, but the green brand image serves as a mediating factor. The environmentally friendly products, along with their trust and preference, enhance the brand image, which contributes to increased loyalty and an intention to purchase the brand. It contributes to the body of theoretical and practical literature on these dynamics in Pakistan, providing a roadmap that enables marketers and policymakers to develop realistic green campaigns and approaches, ensuring sustainability and business development.